Benzedeiras de Maruípe: uma prática de cuidado humano em extinção - Simões, Juliana Pereira (2014)
This is a study of faith healers at one health administrative region of the municipality of Vitória - ES, aiming to identify them, to know their life stories and their interest in articulating with professionals at the local units of primary healthcare. Because it is a region marked by violence arising from drug trafficking, it has become impossible to identify the universe of those women, due to the lack of access to some of these neighborhoods; thus our sample was limited to five faith healers. Material was collected for the study through interviews and observations recorded in a field diary. The transcripts and notes from the diary allowed the narrative of cartographic inspiration for this study. These healers are women between 64-88 years of age, living in austere locations in humble dwellings. Some bless only children, others all those who seek them, including blessing their pets. None of them charges anything, and they do not accept thanks for the provided attention, because according to them the thanks should be directed to God. They are humble women, all old residents of the area, sometimes recognized as important for the gift they have, sometimes rejected as demonic by religious groups. Regarding an approach with local health teams, all the faith healers proved averse to the idea, understanding that such approach would mean an increased and binding demand for blessings, which contradicts the logic of care provided by them, which is only to bless according to convenience: they bless when feeling well, and avoid it when devitalized. Faith healing is endangered of extinction, because the healers are older women, and learning the craft has not been the subject of interest among the younger generations.